Inertia, Resistance, Revolution : Hegel and the Logic of History - Zantvoort, Bart (Contemporary Perspectives in European Philosophy / Zeitgenössische Perspektiven europäischer Philosophie, 2025)
Why are people sometimes unable to change, even if they want to? Why is it so difficult to change political institutions, or to abandon outdated ways of thinking? This book suggests that we can understand the phenomenon of resistance to change in individuals and institutions by returning to Hegel, one of the most influential philosophers of historical and political change. Hegel exposes the paradox inherent in the notion of resistance: on the one hand, resistance to change is necessary to allow for identity and survival in a changing world, and to make stable societies possible; on the other hand, resistance to change also causes obsolete, irrational or repressive ideas and institutions to persist. This book not only presents a theory of inertia, a concept of great importance for philosophy and political theory, but also offers a wide-ranging interpretation of Hegel's philosophy, discussing his views on the will and on habits, on obsolete institutions and revolutionary transformations.